Longitudinal predictors of child sexual abuse in a large community-based sample of South African youth - Meinck, F; Cluver, LD; Boyes, ME (SAGE Publications, 2015)
Sexual abuse has severe negative impacts on children’s lives, but little is known about risk factors for sexual abuse victimization in sub-Saharan Africa. This study examined prospective predictors of contact sexual abuse in a random community-based sample of children aged 10 to 17 years (N = 3,515, 56.6% female) in South Africa. Self-report questionnaires using validated scales were completed at baseline and at 1-year follow-up (96.8% retention rate). Cross-sectional and longitudinal associations between hypothesized factors and sexual abuse were examined. For girls, previous sexual abuse (odds ratio [OR] = 3.44, 95% confidence interval [CI] = [2.03, 5.60]), baseline school dropout (OR = 2.76, 95% CI = [1.00, 6.19]), and physical assault in the community (OR = 2.17, 95% CI = [1.29, 3.48]) predicted sexual abuse at follow-up. Peer social support (OR = 0.84, 95% CI = [0.74, 0.98]) acted as a protective factor. Previous contact sexual abuse was the strongest predictor of subsequent sexual abuse victimization. In addition, peer support moderated the relationship between baseline assault and subsequent sexual abuse. For boys, no longitudinal predictors for sexual abuse victimization were identified. These results indicate that the most vulnerable girls—those not in school and with a history of victimization—are at higher risk for sexual abuse victimization. High levels of peer support reduced the risk of sexual abuse victimization and acted as a moderator for those who had experienced physical assault within the community. Interventions to reduce school drop-out rates and revictimization may help prevent contact sexual abuse of girls in South Africa.